Undergraduate Mathematics Enhanced With Graphing Technology. - M. Ali, Rosihan; Kor, Liew Kee (2004)

(untitled)
The School of Mathematical Sciences at University Sains Malaysia has offered a laboratory course on the integration of hand-held technology into the teaching and learning of mathematics since the beginning of the 2001/2002 academic year.